(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The Standard Of Competence And Skills Required In Each Class In Terms Of The Four Main Types Of Speech Activities Acquired By Teaching The Language To The Student: Listening Comprehension, Speaking, Reading And Writing